2022
DOI: 10.1039/d1dt04312a
|View full text |Cite
|
Sign up to set email alerts
|

Pb2Al2B3O8F3: structure and properties of a new fluoroaluminoborate with non-traditional chain-like B3O8 groups

Abstract: A new fluoroaluminoborate, Pb2Al2B3O8F3, with a non-traditional chain [B3O8]7- was synthesized by high temperature reactions in closed systems for the first time. Different from the traditional [B3O8]7- ring [(3:Δ +...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Therein, the Al–O bonds (1.876(5) and 1.889(5) Å) associated with the edge-sharing of Al–O–Al-O are longer than those of other normal Al–O bonds (1.854 (5) and 1.870 (5) Å), which is beneficial to decrease the repulsion of neighboring Al cations and enhance the stability of edge-sharing [AlO 4 F 2 ] octahedra. It can be named a trans -[AlO 4 F 2 ] unit, since the F atoms are located at the two opposite positions of the [AlO 4 F 2 ] octahedron in Sr 2 Al 2.18 B 5.82 O 13 F 2 , which differs from cis -[AlO 4 F 2 ] unit in Pb 2 Al 2 B 3 O 8 F 3 . In the previous research, few fluoroaluminoborates with excellent optical properties have been reported, and they have been listed in Table S4 in the Supporting Information.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therein, the Al–O bonds (1.876(5) and 1.889(5) Å) associated with the edge-sharing of Al–O–Al-O are longer than those of other normal Al–O bonds (1.854 (5) and 1.870 (5) Å), which is beneficial to decrease the repulsion of neighboring Al cations and enhance the stability of edge-sharing [AlO 4 F 2 ] octahedra. It can be named a trans -[AlO 4 F 2 ] unit, since the F atoms are located at the two opposite positions of the [AlO 4 F 2 ] octahedron in Sr 2 Al 2.18 B 5.82 O 13 F 2 , which differs from cis -[AlO 4 F 2 ] unit in Pb 2 Al 2 B 3 O 8 F 3 . In the previous research, few fluoroaluminoborates with excellent optical properties have been reported, and they have been listed in Table S4 in the Supporting Information.…”
mentioning
confidence: 99%
“…44 Enlightened by these efficient strategies, we attempted to explore the structural regulations via rational structural motif cosubstitution and anticipate achieving novel structures in fluoroaluminoborates. 45 In the previous research, few fluoroaluminoborates with excellent optical properties have been reported, and they have been listed in Table S4 in the Supporting Information. As shown in Figure S1 in the Supporting Information, the similar edge-sharing octahedra can be found in other fluoroaluminoborates 60,61 In addition, there are also some successful cases of various structural motif linkers filled in the single-layer structures.…”
mentioning
confidence: 99%